Pengaruh Problem Based Learning Berbantuan Geogebra Terhadap Kemampuan Pemecahan Masalah Matematis Siswa Materi Perbandingan - Silvia Vernita (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study aimed to determine the effect of the GeoGebra-assisted Problem-Based Learning (PBL) model on students' mathematical problem-solving ability in ratio and proportion. This ability remained low among seventh-grade students at SMP Negeri 13 Jember, particularly in Polya's "looking back" stage, where students often failed to verify their answers. However, previous studies had mostly focused on overall learning outcomes rather than examining the effect on each Polya stage, even though problem-solving abilities might not develop equally across all stages. Therefore, this study employed a quantitative approach with a quasi-experimental design. The population consisted of all seventh-grade students at SMP Negeri 13 Jember. Through cluster random sampling, Class VII-B was selected as the experimental class (GeoGebra-assisted PBL) and Class VII-A as the control class (Direct Instruction). Data collected through tests, observations, and questionnaires were analyzed using the Mann–Whitney U test. The results showed a significant difference between the two classes, with a posttest significance value of 0.000 < 0.05. Thus, it was concluded that the GeoGebra-assisted PBL model significantly affected students' mathematical problem-solving ability and successfully identified which Polya stages developed optimally and which still required reinforcement.
Finalisasi 15 Juli 2026_Yudi
Keywords: Problem Based Learning; GeoGebra; Kemampuan Pemecahan Masalah Matematis; Mathematical Problem-Solving Ability